PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN KOOPERATIF TIPE STAD SISWA KELAS VII-I SMP NEGERI 3 KERTOSONO - Sholihah, Aimmatus (Al Tadib : Jurnal Ilmu Pendidikan, 2015)
Action Research this class as one of the efforts inthe process of learning mathematics through theimplementation of cooperative learning model type STAD,this type has a system of grouping small ie 4 students areheterogeneous, according to the problems faced by students,among others: The low activity of students in activitieslearning, poor learning outcomes of students in learningmathematics. This class action research, aims to increase theactivity and results of learning mathematics. VII-I gradestudents of SMP Negeri 3 Kertosono. With theimplementation procedure of Class Action Research consistsof three cycles, each cycle consists of four stages, namelyPlanning, Implementation, Observation and Reflection.Based on the results of classroom action research, studentmastery of the learning material to show improvement. Thiscan be demonstrated by the average daily test results(average daily tests first without STAD cooperative learning)69 to 72 (daily test II) and 78 (daily test III) after using STADcooperative learning.Keywords: increased activity, learning outcomes, STADcooperative